Distinctive Clinical Features Of Patients With Systemic Sclerosis (Eurasian Medical Research Periodical, 2026)
Systemic sclerosis is a rare, chronic, multisystem autoimmune connective tissue disease in which microvascular injury, immune dysregulation, and progressive fibrosis combine to produce one of the most heterogeneous clinical phenotypes in modern rheumatology. The disease may begin insidiously with Raynaud’s phenomenon, puffy fingers, fatigue, reflux symptoms, or subtle nailfold capillary abnormalities long before a fully classifiable syndrome emerges, yet it can subsequently evolve into a condition marked by skin thickening, digital ischemia, gastrointestinal dysmotility, interstitial lung disease, pulmonary vascular disease, cardiac involvement, renal crisis, musculoskeletal dysfunction, and major impairment in quality of life and survival. The present narrative review aims to synthesize contemporary evidence on the distinctive clinical manifestations of systemic sclerosis, emphasizing the temporal evolution of symptoms, phenotype-based stratification, and the diagnostic significance of early vascular and cutaneous clues. Particular attention is given to the clinical contrast between limited cutaneous and diffuse cutaneous disease, the importance of systemic sclerosis-specific autoantibodies as markers of organ risk rather than mere laboratory labels, and the relevance of very early diagnosis frameworks in patients who present with Raynaud’s phenomenon before overt fibrosis develops. The review also examines the major organspecific manifestations that define disease burden, including esophageal dysfunction, malabsorption, pulmonary fibrosis, pulmonary arterial hypertension, myocarditis-like and arrhythmic phenotypes, and scleroderma renal crisis, together with overlap syndromes and systemic sclerosis sine scleroderma. By integrating classification criteria, cohort data, and recent guideline-based approaches to assessment, this paper argues that the clinical identity of systemic sclerosis is best understood not as a static syndrome but as a dynamic phenotype in which the sequence, clustering, and severity of manifestations determine prognosis and guide surveillance. Recognition of the disease’s characteristic clinical signatures—especially persistent Raynaud’s phenomenon with abnormal capillaroscopy, puffy fingers, digital lesions, telangiectasia, evolving sclerodactyly, early reflux, and unexplained dyspnea—remains central to reducing diagnostic delay and improving outcomes through earlier specialist referral and structured multiorgan screening